Implementation of The Integration of Islam and Science in the Context of Islamic Boarding School - Fahrurrosi, Lingga; Sholihah, Sholihah; Hamid, Abd; Fadhilah, Fadia Putri; Marzuki, Nurmila Binti (STAI Publisistik Thawalib Jakarta, 2025)
The integration of Islam and science in pesantren education is now developing with a transdisciplinary approach using digital technology, such as digital libraries and management systems, to support its practical implementation. This study aims to describe the integration pattern between Islam and science and identify its implementation at Al-Khoirot Islamic Boarding School in Malang. The research uses a descriptive qualitative approach with a case study method. Data were collected through literature review, participatory observation, in-depth interviews with pesantren administrators, staff, and students, and document analysis, then analysed through data reduction, presentation, and conclusion. The results show that the integration of Islam and science at Al-Khoirot pesantren has been successfully applied in several specific areas. This integration is reflected in three main sectors: mapping multidisciplinary educational institutions combining religious studies with science, developing religious literature through an integrated digital library, and utilising digital technology platforms to market products created by students and alumni. However, challenges arise during implementation, including limited human resources, difficulties designing an Islam-science integration curriculum, and technical and infrastructure problems. Conclusion: Implementing Islam and science integration through the digital library faces challenges related to methodology, infrastructure, and digital literacy, thus requiring intensive guidance and a strong curriculum to overcome them.